The Ethnomedicinal Effects of Plants and Herbs Mentioned in Holy Quran and Hadith - Aslam, Mehreen (Journal of Islamic and Religious Studies, 2021)
The present research work is conducted to study the plants, fruits, herbs, and all edibles enlisted in Holy Qur’ān, Aḥādith that have been used by Islamic culture and their health benefits. This paper aims to assemble the latest information about some medicinal edibles and sunnah foods. In the vision of the significance of this study ample data was thoroughly collected from Holy Qur’ān, Aḥādith`s records, Islamic history, and records on the Islamic medicines as well as electronic databases. Current findings are limited to 25 medicinal plants species. Results were systematically arranged of each plant by their English name, along with the botanical names and local names, medicinal uses, and references cited from Holy Holy Qur’ān, Aḥādith, and Islamic books in view of latest scientific research studies. It has been proved that Eras ago, Holy Qur’ān has cited the valuable resources of many foodstuffs, and nowadays scientists have established a portion of them through many studies, which helps to appreciate the vastness of Allah. The paper concludes that the Qur’ān has cited the treasured properties of many foods in preventing diseases, today researchers have recognized a part of them through many experiments, it helps to apprehend the greatness of Allah.